Feasibility of a Web-Based Psychoeducation Course and Experiences of Caregivers Living With a Person With Schizophrenia Spectrum Disorder: Mixed Methods Study - Laine Anna; Anttila Minna; Hirvonen Heli; Välimäki Maritta (JMIR PUBLICATIONS, INC, 2022)
Background: Schizophrenia is a severe mental illness that burdens both patients and caregivers.Objective: The aim of this study is to examine the feasibility of a web-based psychoeducation course targeted at caregivers of persons with schizophrenia spectrum disorders (SSDs) and to describe their experiences of living with a person with SSD based on the material caregivers produced during the web-based course.
Methods: A convergent, parallel, mixed methods study design was used. First, caregivers' engagement in the course was evaluated quantitatively. Second, the overview of the course feedback was evaluated using quantitative and qualitative methods. Third, the experiences of being a caregiver to a person with SSD were analyzed qualitatively with the thematic analysis of the writings caregivers produced during the web-based course.
Results: A total of 30 caregivers participated in the study and a web-based psychoeducation course. Less than two-thirds (18/30, 60%) completed the course. Content was most often logged for the first module, Orientation (3465 log-ins), and the lowest number of log-ins was recorded for the Daily life module (1061 log-ins). Feedback on the course varied; over half (10/17, 59%) of the caregivers considered the content to be very good or good, about half (9/17, 53%) considered the website layout to be good, only 6% (1/17) felt that the usability of the website was poor, and no one felt that it was very poor. From the reported experiences of being a caregiver to a person with SSD, 3 themes were formed: the caregiver's own well-being, relationship with the person with SSD, and experience of health care services.
Conclusions: The web-based psychoeducation course for caregivers living with a person with SSD seems to be especially suitable for those who have little experience as a caregiver. In the future, more planning and the consideration of aspects related to the needs of specific target groups, course content, practical arrangements, and scheduling should be taken into account. In addition, although caregivers can improve their own well-being in different ways, they need regular support and cooperation from health care professionals.